ACSM's resources for the personal trainer - Edwards, Elizabeth Skidmore; Hargens, Trent; Musto, Anthony A.; Piercy, Katrina (Wolters Kluwer, 2022)
"Certified Personal Trainer candidates looking to boost their exam confidence, as well as practicing Personal Trainers who want to take their An essential resource to prepare for the ACSM Certified Personal Trainer examination, ACSM's Resources for the Personal Trainer, Sixth Edition, provides critical insights for Certified Personal Trainer candidates looking to boost their exam confidence, as well as practicing Personal Trainers who want to take their practice to the next level. This updated edition is fully aligned with the eleventh edition of ACSM's Guidelines for Exercise Testing and Prescription and equips readers with the latest practices in client screening, exercise program development, and working with special populations"--